The World of Niagara Wine - Fullerton, Christopher Adam, 1970-; Mackintosh, Phillip Gordon, 1960-; Ripmeester, Michael R. (Michael Robert), 1962- (Book collections on Project MUSE., 2013)
A transdisciplinary exploration of the Niagara wine industry. It explores the history and regulation of wine production as well as its contemporary economic significance. It examines the social and cultural ramifications of Niagara's reliance on grapes and wine as an economic motor for the region.